Fouling reduction in nanofiltration membranes in the treatment of municipal sewage – effect of coagulant type used for prior chemically enhanced primary treatment. (21st October 2022) - Fida, Sadia; Haydar, Sajjad; Zeeshan, Muhammad
Abstract: The limiting factor in wide-scale application of membranes for wastewater treatment is membrane fouling. Coagulation has emerged as an effective technique for fouling control. In this research, municipal wastewater was treated using a two-stage treatment. In stage-1, chemically enhanced primary treatment (CEPT) was rendered using an optimum dose of two coagulants, i.e. alum, ferric chloride and a 1:1 mix of both. The optimum doses for coagulants were determined using a jar test. In stage-2, a nanofiltration (NF) membrane was used to further treat the effluent from stage-1. In CEPT, the 1:1 mixture of coagulants showed maximum removals, i.e. 75–77% for the total suspended solids and 73–75% for the chemical oxygen demand (COD). Stage-2 provided 85–95% removals for turbidity (0.88 nephelometric turbidity units), COD (41 mg/L), total dissolved solids (101 mg/L), hardness (11 mg/L as CaCO3 ), chlorides (80 mg/L), and heavy metals (copper [0.03 mg/L] and lead [0.02 mg/L]). The operational time of the NF membrane was 46 min, 55 min and 70 min using alum, ferric chloride, and mix (1:1), respectively. Significant reduction was observed in membrane fouling for 1:1 mixture of coagulants. The effluent met the US Environmental Protection Agency guidelines for non-potable reuse. HIGHLIGHTS: Coagulants (alum and ferric chloride) give best results when used in a 1:1 mix. Up to 95% removal of turbidity, COD, TDS, and heavy metals using chemically enhanced primary treatment and nanofiltration. CEPT is an effective technique for NF membrane fouling control. NF membrane run time is 1.5 and 1.3 times higher when coagulants are used in a mix rather than when used separately. Effluent met the USEPA guidelines for non-potable reuse. Graphical Abstract